Quality Management Through Industry 4.0 in Construction Companies - SHAMIM, JAHED KAMBIZ (İstanbul Kültür Üniversitesi, 2023)
Turn to industry4.0 tools and industrialization for quality management is require for today's construction companies, due to difficulties and waste of time, money in construction companies, that the entire construction companies face up the importance of industry 4.0 through quality management has become more peremptory than ever. The main aim of the study is to select the best alternative Industry 4.0 application to be implemented in construction companies in Middle East. For this purpose, three experts are surveyed to obtain their point of view about the volubility of the criteria that could be considered in the alternative selection process, and the relative importance of each alternative in accordance with each criterion. A hybrid methodology based on Analytic Hierarchy Process (AHP) and TOPSIS is implemented, and the best alternative is selected. Nowadays environment require modern and comfort constructions (buildings, pavements, bridges, dams), therefore companies have to adapt quality management through industry 4.0 tool. Construction companies in which countries of middle east are more applicable for industry 4.0 tools? Does industry 4.0 provide facilities in construction companies? According to this study cyber-physical system were found to be most suitable alternative, Big data & cloud computing was ranked second in middle east countries.
İnşaat Şirketlerinde Endüstri 4.0 İle Kalite Yönetimi
▪ Yüksek lisans tezi.
Keywords: Construction 4.0; MCDM; Industry 4.0; AHP; TOPSIS